CAUSES AND PREVENTION OF JUVENILE DELINQUENCY - Dr. Smritikana Ghosh (Galaxy International Interdisciplinary Research Journal, 2021)
In India, juvenile delinquency is a major issue, with the majority of young people losing their lives as a result of it. Teenage criminality and related issues have a variety of repercussions for the kids involved, as well as for their families and the whole community. In addition to having an impact on the victims of crime, the issue also has an impact on the family of the juvenile delinquent, their future, and the community as a whole. The victims of juvenile delinquency are the most visible individuals who are impacted by it. Children and adolescents suffer the most severe consequences of their crimes because of the socio-economic and psychological difficulties that they cause in their families and in society as a result of their actions. Those under the age of majority who commit severe crimes do so in order to protest perceived injustices that have been committed against them in the past. This causes individuals to suffer from psychological depression, which in turn leads to their committing additional crimes. As a result, it is important to do research on the prevalence of juvenile delinquency in order to identify and evaluate the reasons from a psychological standpoint, as well as to eradicate the problem from society.